2014
DOI: 10.1152/jn.00673.2013
|View full text |Cite
|
Sign up to set email alerts
|

Long-latency, inhibitory spinal pathway to ankle flexors activated by homonymous group 1 afferents

Abstract: Zewdie ET, Roy FD, Okuma Y, Yang JF, Gorassini MA. Long-latency, inhibitory spinal pathway to ankle flexors activated by homonymous group 1 afferents. J Neurophysiol 111: 2544 -2553, 2014. First published March 26, 2014 doi:10.1152/jn.00673.2013.-Inhibitory feedback from sensory pathways is important for controlling movement. Here, we characterize, for the first time, a longlatency, inhibitory spinal pathway to ankle flexors that is activated by low-threshold homonymous afferents. To examine this inhibitory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This may be a consequence of the afferent input stimulated by PES, which might cancel out the effects of the subsequent iTBS on motor cortex excitability. Indeed, previous studies have indicated that afferent stimulation from the CPN suppresses MEPs induced by single-pulse TMS ( Roy and Gorassini, 2008 ; Zewdie et al, 2014 ). Similarly, the effects of TBS over the motor cortex of the upper limb are known to be modulated or even blocked by muscle activation that occurs around the time of TBS stimulation ( Huang et al, 2008 ; Goldsworthy et al, 2012 ; Huang, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be a consequence of the afferent input stimulated by PES, which might cancel out the effects of the subsequent iTBS on motor cortex excitability. Indeed, previous studies have indicated that afferent stimulation from the CPN suppresses MEPs induced by single-pulse TMS ( Roy and Gorassini, 2008 ; Zewdie et al, 2014 ). Similarly, the effects of TBS over the motor cortex of the upper limb are known to be modulated or even blocked by muscle activation that occurs around the time of TBS stimulation ( Huang et al, 2008 ; Goldsworthy et al, 2012 ; Huang, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one group, the size of MEPs elicited during paired stimulation was reduced and in these subjects PCMSϪ reduced corticospinal excitability, whereas, in a second group, the size of MEPs elicited during paired stimulation when applying PCMSϪ was similar to MEP-max and in these subjects paired stimulation was ineffective at reducing corticospinal excitability. Evidence showed that electrical stimulation of homonymous and heteronymous nerves at the knee and/or at the ankle as well as stimulation of the skin innervated by the deep peroneal nerve, which contains the cutaneous branch of the common peroneal nerve, suppresses the TA MEP size 20 -40 ms before a TMS pulse over the leg motor cortex (Kasai et al 1992;Roy and Gorassini 2008;Roy et al 2010;Zewdie et al 2014). This is consistent with the results from our control experiment showing that a conditioning pulse to the common peroneal nerve, given 20 -40 ms before TMS, decreased TA MEP size.…”
Section: Discussionmentioning
confidence: 99%
“…3, B and D) and in these individuals MEPs were suppressed after PCMSϪ; therefore, we refer to these subjects as responders (control R ). Evidence showed that PNS of the common peroneal nerve applied 20 -40 ms before a TMS pulse suppressed the size of the TA MEP (Kasai et al 1992;Roy and Gorassini 2008;Roy et al 2010;Zewdie et al 2014). During PCMSϪ, for volleys to arrive at the spinal motoneurons 15 ms before descending volleys, we used an ISI between PNS and TMS of~20 ms. To determine the best interval for suppressing the TA MEP in control NR during PCMSϪ, we completed an additional control experiment in which we examined the effect of PNS of the common peroneal nerve 20, 30, and 40 ms before the TMS pulse.…”
Section: Methodsmentioning
confidence: 99%
“…Cervical stimulation may improve walking function by inducing arm-leg synchronizations, 33 , 50 activating propriospinal pathways, 34 and directly modulating supraspinal inputs by recruiting the corticospinal tract. 51 …”
Section: Discussionmentioning
confidence: 99%